2004
DOI: 10.1080/02841850410008261
|View full text |Cite
|
Sign up to set email alerts
|

Breast arterial calcifications as an indicator of systemic vascular disease

Abstract: Screening mammograms might be useful in the detection of women at risk for systemic vascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…The study period ranged from 1995 to 2011, and the studies looked at relation between BAC and CVD, cardiovascular (CV) mortality, coronary, cerebral or systemic atherosclerosis, CIMT, and coronary calcium. We found 19 studies 725 looking at the association of BAC and CAD and/or CVD, 8 studies between BAC and stroke, 79,20,21,23,24,26 2 studies between BAC and PAD, 27,28 3 studies between BAC and CIMT, 16,19,29 and 2 studies between BAC and coronary artery calcification (CAC). 30,31 Tables 1 and 2 show detailed information regarding individual studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study period ranged from 1995 to 2011, and the studies looked at relation between BAC and CVD, cardiovascular (CV) mortality, coronary, cerebral or systemic atherosclerosis, CIMT, and coronary calcium. We found 19 studies 725 looking at the association of BAC and CAD and/or CVD, 8 studies between BAC and stroke, 79,20,21,23,24,26 2 studies between BAC and PAD, 27,28 3 studies between BAC and CIMT, 16,19,29 and 2 studies between BAC and coronary artery calcification (CAC). 30,31 Tables 1 and 2 show detailed information regarding individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were 2 studies showing the association between BAC and PAD, 27,28 3 between BAC and CIMT, 16,19,29 and 2 between BAC and CAC. 30,31 Table 2 shows description of the studies along with their ORs and 95% CIs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Screening mammography is recognized as the most important tool for the detection of breast cancer (17,18).It has been suggested that breast arterial calcification (BAC) seen on mammography could be an indicator of generalized vascular disease (19,20).…”
Section: Discussion:-mentioning
confidence: 99%